2007
DOI: 10.1016/j.vaccine.2006.11.049
|View full text |Cite
|
Sign up to set email alerts
|

A papillomavirus-like particle (VLP) vaccine displaying HPV16 L2 epitopes induces cross-neutralizing antibodies to HPV11

Abstract: Peptides of the papillomavirus L2 minor capsid protein can induce antibodies (Ab) that neutralize a broad range of human papillomavirus (HPV) genotypes. Unfortunately, L2 is antigenically subdominant to L1 in the virus capsid. To induce a strong anti-L2 Ab response with cross-neutralizing activity to other mucosal types, chimeric virus-like particles (VLP) were generated in which HPV16 L2 neutralization epitopes (comprising L2 residues 69-81 or 108-120) are inserted within an immunodominant surface loop (betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 58 publications
2
86
0
3
Order By: Relevance
“…Our data are consistent with the finding that targeting the N terminus is neutralizing at a stage after binding and entry. The role of L2 during early entry has been shown to be primarily after virus binding and has been attributed to the findings that parts of the N terminus of L2 seem to loop out of the viral capsid in the fully formed particle or are exposed after a conformational change that occurs after the virus binds to the target cells (29,30,32,36,41,43,46,48,52). It was previously suggested that the L2 region encompassing residues 41 to 44 was exposed on the outside of pseudoviral particles using an enzyme-linked immunosorbent trap assay (30), but this has not been confirmed by EM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data are consistent with the finding that targeting the N terminus is neutralizing at a stage after binding and entry. The role of L2 during early entry has been shown to be primarily after virus binding and has been attributed to the findings that parts of the N terminus of L2 seem to loop out of the viral capsid in the fully formed particle or are exposed after a conformational change that occurs after the virus binds to the target cells (29,30,32,36,41,43,46,48,52). It was previously suggested that the L2 region encompassing residues 41 to 44 was exposed on the outside of pseudoviral particles using an enzyme-linked immunosorbent trap assay (30), but this has not been confirmed by EM.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested by enzyme-linked pseudovirion capture assay using an L2 antibody that HPV type 16 residues 14 to 144 and in particular residues 32 to 81 are likely to reside on the surface of the viral capsid (30). These EM and neutralization data have led to several studies addressing the use of papillomavirus L2 sequences as vaccine targets for specific and multiple PV genotypes since the regions of L2 shown to be exposed on the capsid surface are more conserved than the loops of the L1 protein (29,30,36,43,48). In addition, there is evidence that upon cell binding, a conformational change allows for the exposure of hidden L2 residues that can serve as neutralizing epitopes (41,46,52).…”
mentioning
confidence: 99%
“…An alternative strategy to broaden the protection of HPV vaccines that is also being considered is to use conserved epitopes from the L2 minor capsid protein incorporated into HPV L1 VLPs (22)(23)(24)(25)(26)(27)(28)(29). This strategy is supported by evidence that vaccines based on L2 peptides can confer broad protection in mouse or rabbit HPV challenge models and elicit neutralizing antibodies against a wide range of HPVs (27,(29)(30)(31)(32)(33).…”
mentioning
confidence: 99%
“…A number of different VLPs were shown to be highly immunogenic antigen carriers capable of inducing humoral immune responses. For example, VLPs expressing proteins from influenza virus, papillomavirus, and rotavirus all induce high titers of neutralizing or protective antibodies (25,28,35). Some VLPs were also shown to induce CTL responses.…”
mentioning
confidence: 99%